2008
DOI: 10.1007/s12098-008-0150-2
|View full text |Cite
|
Sign up to set email alerts
|

A study of acute febrile encephalopathy with special reference to viral etiology

Abstract: The etiology of acute febrile encephalopathy varies from infectious etiologies to noninfectious metabolic disorders. There are no distinguishing clinical or radiological features to differentiate the various causes of viral encephalitis. The clinical and the radiological findings in encephalitis should be interpreted in the geographical and other epidemiological background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
57
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 14 publications
12
57
2
Order By: Relevance
“…In the current study signs of meningeal irrita on were evaluated in 46 children who were of more than two years of age among whom posi ve results were seen in 50% of children similar to that observed by Karmakar et al 10 and to correlate clinical and radiological features of pa ents with viral encephali s.\n\nMETHODS: A prospec ve hospital based study conducted on the consecu ve pa ents admi ed in a pediatric unit during the period of 1(st In our study, neck s ff ness was present in 46.3% of children. Various authors have reported diff erent frequencies of neck s ff ness ranging from 30% to 50% of children with febrile encephalopathy 2,12 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the current study signs of meningeal irrita on were evaluated in 46 children who were of more than two years of age among whom posi ve results were seen in 50% of children similar to that observed by Karmakar et al 10 and to correlate clinical and radiological features of pa ents with viral encephali s.\n\nMETHODS: A prospec ve hospital based study conducted on the consecu ve pa ents admi ed in a pediatric unit during the period of 1(st In our study, neck s ff ness was present in 46.3% of children. Various authors have reported diff erent frequencies of neck s ff ness ranging from 30% to 50% of children with febrile encephalopathy 2,12 .…”
Section: Discussionsupporting
confidence: 83%
“…As noted by Khinchi et al from Nepal, this study also revealed increased number of cases during the monsoon season of July to August which may be due to the increase transmission of the diseases during the monsoon months 13 . Similarly acute febrile encephalopathy was found to occur more frequently in people of low socioeconomic status in our country, present in 32 (59%) children, which was similar to that noted in India 10 and to correlate clinical and radiological features of pa ents with viral encephali s.\n\nMETHODS: A prospec ve hospital based study conducted on the consecu ve pa ents admi ed in a pediatric unit during the period of 1(st. This could be because increased incidence of overcrowding, poor hygiene, poor nutri onal status and subop mal immunity increases suscep bility to various infec ous diseases, febrile encephalopathy being one of them.…”
Section: Discussionsupporting
confidence: 79%
“…Similar sex prevalence ratio (M:F=1.7:1), where males were commonly involved than females in 1-5 years of age group and 6-14 years of age group, whereas males and females show equal incidence in 2 months-1year of age group was observed in a study by Karmarkar SA et al in 2008. 8 Out of 84 patients studied, 32 cases (38%) were diagnosed as viral encephalitis which was the most common etiology for febrile encephalopathy. Similar observations were found in a study by Karmarkar SA et al in 2008 which showed 37.3% of viral encephalitis cases.…”
Section: Discussionmentioning
confidence: 99%
“…8 Morbidity in relation to etiology are, out of 32 cases of viral encephalitis-persistent seizures were seen in 3 (9.3%) cases, bulbar palsy and hemiparesis in 2 (6.2%) cases each, dysarthria and cranial nerve palsy was observed in 1 (3.2%) case. Overall morbidity was 28.1% which was similar to study by Karmarkar SA et al 8 Total morbidity rate was 33.3% and out of 29 cases of pyogenic meningitis, causes of morbidity are persistent seizures which was seen in 3 (10.3%) cases; bulbar palsy, hemiparesis, dysarthria and cranial nerve palsy are seen in 1 (3.4%) case. In the same study done by Karmarkar SA et al, out of 8 cases of cerebral malaria, persistent seizures are the leading cause of morbidity which was observed in 1 (12.5%) case and out of 6 cases of Tuberculous meningitis, hydrocephalus and cranial nerve palsy are the leading causes of morbidity accounting for 1 (16.6%) case each.…”
mentioning
confidence: 99%
See 1 more Smart Citation